Antistatic polyethylene composite film and preparation method thereof

By using multi-layer structure and modified graphene technology in polyethylene films, combined with silver nanoparticles and flame retardant, the problem of insufficient mechanical and antistatic properties of polyethylene films is solved, and efficient electrostatic charge conduction and resistance are achieved Burning effect, suitable for a variety of high-tech applications.

CN119189466AActive Publication Date: 2024-12-27JIANGYIN PINJIA PLASTIC IND CO LTD

Patent Information

Application Number
CN202411306790.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

The existing polyethylene films have shortcomings in mechanical properties and antistatic properties, which lead to prone to fracture and accumulation of static electricity, affecting their application in high-tech industries.

Method used

Antistatic polyethylene composite film designed with multi-layer structure, the surface layer and heat sealing layer contain low-density polyethylene, ultra-high molecular weight polyethylene, antistatic agent and flame retardant. Graphene oxide is prepared by the Hummers method and on its surface Introduce isocyanate and benzotriazole groups to form silver nanoparticles, enhance the electrostatic charge conduction and dispersion capabilities, and use modified aluminum hydroxide, phosphophenyl/triazine bisyl synergistic flame retardant and expanded graphite to improve flame retardant performance.

Benefits of technology

It achieves durability and uniformity of antistatic properties, improves the mechanical strength and flame retardant properties of the film, and meets the needs of a variety of application scenarios.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of polyethylene film preparation, in particular to an antistatic polyethylene composite film and a preparation method thereof.The polyethylene composite film is sequentially provided with a heat sealing layer, a blocking layer and a surface layer from inside to outside, and the surface layer and the heat sealing layer are prepared from, by weight, 55-65 parts of low-density polyethylene, 5-10 parts of polyethylene, 5-10 parts of polyethylene, 5-10 parts of polyethylene and 5-10 parts of polyethylene. 9-12 parts of ultra-high molecular weight polyethylene, 1-3 parts of a compatilizer, 6-10 parts of an antistatic agent and 8-15 parts of a flame retardant; and the barrier layer is made of ethylene-vinyl alcohol copolymer resin. The antistatic polyethylene composite film provided by the invention realizes excellent and lasting antistatic performance, the antistatic agent uniformly distributed in the film ensures rapid conduction and dispersion of electrostatic charges, and the problem of non-uniform antistatic performance is effectively solved; meanwhile, by introducing benzotriazole groups and silver nanoparticles, a stable antistatic network structure is formed, and the durability of the antistatic effect is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyethylene film preparation, and in particular to an antistatic polyethylene composite film and a preparation method thereof. Background Art

[0002] Polyethylene film refers to a film produced from polyethylene particles. In the existing process, multi-layer film co-extrusion is generally carried out based on polyethylene film to obtain a multi-layer composite polyethylene film. Polyethylene is widely used in composite packaging because of its good heat sealing properties, impact resistance, certain transparency and barrier properties. With the continuous progress of society, our demand for the application of polyethylene film is increasing and the scope is becoming wider. Therefore, simple polyethylene film is far from meeting the needs of social development. Under certain conditions, traditional polyethylene film is prone to breakage and damage due to the mechanical properties that do not meet the requirements; and due to the characteristics of the polymer nature, it is easy to accumulate static electricity and even cause serious accidents such as fire; these limit the application of polyethylene film in future high-tech industries, so improving the mechanical properties and antistatic properties of polyethylene film has become a research focus.

[0003] The existing patent CN201510628031.6 discloses a polyethylene composition and an antistatic film, wherein the polyethylene composition contains a conductive filler, component A, component B and component C; the component A is a linear low-density polyethylene of ethylene / α-olefin copolymer, and its melt index MIA at a temperature of 190°C and a load of 2.16 kg is 0.01-2 g / 10 min, and the density ρA is 0.880-0.936 g / cm 3 Component B is a linear low-density polyethylene of ethylene / α-olefin copolymer, having a melt index MIB of 2.1-14.9 g / 10 min at a temperature of 190°C and a load of 2.16 kg, and a density ρB of 0.910-0.930 g / cm 3 Component C is a linear low-density polyethylene of ethylene / α-olefin copolymer, having a melt index MIC of 15-150 g / 10 min at a temperature of 190°C and a load of 2.16 kg, and a density ρC of 0.880-0.930 g / cm 3 . When the polyethylene composition is prepared into a polyethylene film by a flat film stretching method, not only the stretching ratio is large and the film-forming rate is high, but also the obtained film has good antistatic properties. However, the above technical scheme mainly relies on conductive fillers to achieve antistatic effects, and there may be a problem that the antistatic effect may not be durable enough. Some conductive fillers (such as metal particles and metal fibers) may have the risk of migration or falling off, affecting the durability of the antistatic performance; at the same time, some conductive fillers (such as carbon nanotubes and metal particles) may have agglomeration problems, resulting in uneven distribution of antistatic properties on the surface of the film. Summary of the invention

[0004] In view of this, the present invention proposes an antistatic polyethylene composite film and a preparation method thereof to solve the problems of uneven antistatic performance and short-lasting antistatic effect in the prior art.

[0005] The technical solution of the present invention is implemented as follows: The present invention provides an antistatic polyethylene composite film, which is provided with a heat-sealing layer, a barrier layer and a surface layer in sequence from the inside to the outside, and the raw materials of the surface layer and the heat-sealing layer include the following components in parts by weight:

[0006] 55-65 parts of low-density polyethylene, 9-12 parts of ultra-high molecular weight polyethylene, 1-3 parts of compatibilizer, 6-10 parts of antistatic agent and 8-15 parts of flame retardant; the barrier layer is ethylene-vinyl alcohol copolymer resin.

[0007] On the basis of the above technical solution, preferably, the preparation method of the antistatic agent comprises the following steps:

[0008] S1. Graphene oxide is prepared by Hummers method. Graphene oxide is dispersed in DMF, 2,5(2,6)-bis(isocyanate methyl)bicyclo[2.2.1]heptane is added, and the mixture is stirred at 60-100° C. for 1-4 h. The reaction product is washed, centrifuged and dried to obtain isocyanate-modified graphene.

[0009] S2, dispersing the isocyanate-modified graphene in DMF, ultrasonically dispersing for 20-30 minutes, adding 5-carboxybenzotriazole and a catalyst, stirring the reaction mixture at 70-85° C. for 16-20 hours under nitrogen protection, cooling to room temperature after the reaction is completed, washing, centrifuging and drying the reaction product to obtain benzotriazole-modified graphene;

[0010] S3, dispersing the benzotriazole-modified graphene in DMF, adding silver nitrate, ultrasonically stirring, adding a reducing agent, stirring for reaction, washing, centrifuging and drying the reaction product, and obtaining the antistatic agent.

[0011] In the present invention, in step S1, graphene oxide is prepared by the Hummers method, and a large number of oxygen-containing functional groups, such as hydroxyl, epoxy and carboxyl groups, are introduced on the surface of graphene sheets. The oxygen-containing groups (mainly hydroxyl groups) on the surface of graphene oxide react with isocyanate groups to form carbamate bonds (-NH-COO-). The rigid structure of 2,5(2,6)-di(isocyanatemethyl)bicyclo[2.2.1]heptane helps to maintain the distance between graphene sheets; at the same time, the introduced organic groups can produce better interactions with polyethylene molecular chains to improve the interfacial bonding force. In step S2, the carboxyl group (-COOH) in 5-carboxylbenzotriazole reacts with the residual isocyanate group (-N=C=O) to introduce the benzotriazole group into the surface of the modified graphene. The benzotriazole group and the residual sp2 region on the surface of the graphene oxide can form a π-π stacking effect, thereby enhancing the degree of delocalization of electrons in the entire system. The π-π conjugation enhancement effect can improve the electron transport capacity of the entire system, contribute to the rapid dispersion and conduction of static charges, and thus improve the antistatic properties of the material. In addition, the π-π conjugation effect may affect the dispersion behavior of the modified graphene oxide in the polymer matrix, so that the antistatic properties can be more evenly distributed throughout the material. In step S3, silver ions nucleate and grow on the surface of modified graphene under the action of a reducing agent to form silver nanoparticles, which can quickly conduct and disperse static charges, prevent static electricity accumulation, and further improve the antistatic performance; the benzotriazole group forms uniformly distributed coordination sites on the graphene surface, forms a stable chelate with the silver ions, and promotes the silver nanoparticles to form a more uniform and stable distribution on the graphene surface, thereby further improving the durability of the antistatic performance.

[0012] Based on the above technical solution, preferably, in step S1, the mass volume ratio of graphene oxide and 2,5(2,6)-bis(isocyanatemethyl)bicyclo[2.2.1]heptane is 90-110 mg:2.5-3.5 mL.

[0013] On the basis of the above technical solution, preferably, in step S2, the mass ratio of isocyanate-modified graphene, 5-carboxybenzotriazole and catalyst is 1:1.5-2:0.1-0.2, and the catalyst is 1,4-diazabicyclo[2.2.2]octane.

[0014] On the basis of the above technical solution, preferably, in step S3, the mass ratio of benzotriazole-modified graphene, silver nitrate and reducing agent is 1:0.5-2:1-2, and the reducing agent is vitamin C or sodium borohydride.

[0015] On the basis of the above technical solution, preferably, the flame retardant, by weight, includes 6-8 parts of modified aluminum hydroxide, 1-3 parts of phosphaphenanthrene / triazine dibase synergistic flame retardant and 2-4 parts of expanded graphite.

[0016] On the basis of the above technical scheme, preferably, the preparation method of the modified aluminum hydroxide comprises the following steps: dispersing nano aluminum hydroxide in deionized water, adding aluminum triacetylacetonate after uniform dispersion, reacting at 70-80° C. for 2-4 hours, filtering, washing and drying the reaction product to obtain modified aluminum hydroxide.

[0017] In the present invention, aluminum hydroxide is surface-modified, and aluminum triacetylacetonate reacts with the hydroxyl group on the surface of aluminum hydroxide to form an organic coordination layer on the surface of aluminum hydroxide. The organic coordination layer acts as a "bridge" between aluminum hydroxide and the polyethylene matrix, and can improve the compatibility of the inorganic filler with the organic polymer matrix. The modified aluminum hydroxide provides basic flame retardancy and smoke suppression, the phosphaphenanthrene / triazine bi-base synergistic flame retardant enhances the gas phase and condensed phase flame retardancy, and the expanded graphite improves the overall thermal stability by forming a worm-like insulation layer. The carbon layer formed by the phosphorus-based flame retardant combines with the aluminum oxide layer generated by the decomposition of aluminum hydroxide to form a stronger protective barrier. The three components work synergistically to further improve the flame retardancy efficiency.

[0018] On the basis of the above technical solution, preferably, the mass ratio of the nano aluminum hydroxide to aluminum triacetylacetonate is 1:8-12.

[0019] On the basis of the above technical solution, preferably, the compatibilizer is any one of maleic anhydride grafted polyethylene and ethylene-acrylic acid copolymer.

[0020] On the other hand, the present invention provides a method for preparing an antistatic polyethylene composite film, comprising the following steps:

[0021] (1) According to the raw material formula of the heat seal layer, the barrier layer and the surface layer, the master batch is respectively batched, mixed and dried for pretreatment; the raw materials of each layer are respectively put into the corresponding twin-screw extruder, and the temperature of the heating zone of the twin-screw extruder is controlled to be 180-200° C., and the melt co-extruded from the die head of the three layers is cooled and solidified on the surface of the casting roller to obtain a cast sheet;

[0022] (2) The cast sheet is longitudinally stretched, the temperature during longitudinal stretching is controlled to be 110-120°C, the ratio is 3.5-4:1, and the first heat setting is performed, the temperature of the first heat setting is controlled to be 120-130°C, and the time is 5-6s; then the cast sheet is transversely stretched, the temperature during transverse stretching is controlled to be 120-130°C, the ratio is 3-3.5:1, and the second heat setting is performed, the temperature of the second heat setting is controlled to be 110-120°C, and the time is 4-5s. After the second heat setting is completed, an antistatic polyethylene composite film is obtained.

[0023] The antistatic polyethylene composite film and the preparation method thereof of the present invention have the following beneficial effects compared with the prior art:

[0024] (1) The antistatic polyethylene composite film provided by the present invention achieves excellent and lasting antistatic performance through multi-layer structure design and special antistatic agent. The antistatic agent evenly distributed in the surface layer and heat sealing layer of the film ensures the rapid conduction and dispersion of static charge, effectively solving the problem of uneven antistatic performance; at the same time, by introducing benzotriazole groups and silver nanoparticles on the surface of modified graphene, a stable antistatic network structure is formed, which greatly improves the durability of the antistatic effect; in addition, the film also has good flame retardant properties and mechanical strength, meeting the needs of various application scenarios;

[0025] (2) Through the introduction of isocyanate modification, benzotriazole groups and silver nanoparticles, not only the antistatic effect is improved, but also the uniform distribution and long-term stability of the antistatic performance in the polyethylene matrix are ensured; the isocyanate modification improves the compatibility of graphene with the polyethylene matrix, ensuring the stable dispersion of the antistatic agent in the polyethylene; the π-π stacking effect of the benzotriazole group further enhances the degree of electron delocalization, and the composite of isocyanate-modified graphene and 5-carboxybenzotriazole forms a stable antistatic network structure, which makes it difficult to migrate or degrade in the polyethylene matrix, ensuring a long-term antistatic effect; the introduction of silver nanoparticles enhances the charge conduction ability and forms a continuous and effective conductive network. At the same time, the benzotriazole group can make the silver nanoparticles evenly and stably distributed on the surface of the modified graphene through chelation, further improving the durability of the antistatic performance;

[0026] (3) The flame retardant system adopted in the present invention includes modified aluminum hydroxide, phosphaphenanthrene / triazine bibase synergistic flame retardant and expanded graphite, forming a synergistic flame retardant effect; the modified aluminum hydroxide improves the compatibility with the polyethylene matrix through surface modification and enhances the flame retardant effect, the phosphaphenanthrene / triazine bibase synergistic flame retardant works in both the gas phase and the condensed phase, and the expanded graphite improves the overall thermal stability by forming a worm-like insulation layer. This multi-component synergistic effect improves the flame retardant efficiency and improves the overall performance of the material. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Unless otherwise specified, the raw materials used in the following examples and comparative examples are all commercially available.

[0029] Low-density polyethylene was purchased from Dongguan Jinshixiang Plastic Raw Materials Co., Ltd., brand 1905UMS, melt flow rate: 5g / 10min, density: 0.919g / cm 3 ; Ultra-high molecular weight polyethylene was purchased from Dongguan Hongkuo Plastic Co., Ltd., and the final product was UHMWPE, model X201; expanded graphite was purchased from Qingdao Mingrun Chenyue Graphite Co., Ltd., with a specification of 80 mm and a flake size of 0.18 mm. The phosphaphenanthrene / triazine bi-based synergistic flame retardant was obtained by ring-opening reaction of 9,10-dihydro-9-oxo-10-phosphaphenanthrene-10-oxide (DOPO) and 1,3,5-triglycidyl isocyanurate (TGIC).

[0030] Example 1

[0031] This embodiment provides an antistatic polyethylene composite film and a preparation method thereof, which specifically comprises the following steps:

[0032] The antistatic polyethylene composite film includes a heat-sealing layer, a barrier layer and a surface layer, wherein the raw materials of the surface layer and the heat-sealing layer include the following components: 600g of low-density polyethylene, 110g of ultra-high molecular weight polyethylene, 20g of maleic anhydride grafted polyethylene, 80g of antistatic agent and 110g of flame retardant; the barrier layer is ethylene-vinyl alcohol copolymer resin.

[0033] Wherein, the preparation method of the antistatic agent comprises the following steps:

[0034] S1. Prepare graphene oxide by Hummers method. Disperse 10 g of graphene oxide in 100 mL of DMF, add 0.3 L of 2,5(2,6)-di(isocyanate methyl)bicyclo[2.2.1]heptane, and stir the reaction at 80° C. for 2.5 h under nitrogen protection. After the reaction, wash the reaction product with DMF three times, centrifuge at 6000 rpm for 15 min to collect the product, and dry the collected product in vacuum at 50° C. for 12 h to obtain isocyanate-modified graphene.

[0035] S2, dispersing 10g of isocyanate-modified graphene in 100mL DMF, ultrasonically dispersing for 25min, adding 18g of 5-carboxybenzotriazole and 1.5g of 1,4-diazabicyclo[2.2.2]octane, stirring the reaction mixture at 80°C for 18h under nitrogen protection, cooling to room temperature after the reaction, washing the reaction product with DMF and ethanol for 3 times respectively, collecting the product by centrifugation at 10000rpm for 30min, and vacuum drying the collected product at 70°C for 48h to obtain benzotriazole-modified graphene;

[0036] S3. Disperse 10 g of benzotriazole-modified graphene in 200 mL of DMF, add 15 g of silver nitrate, stir ultrasonically for 25 min, add 15 g of vitamin C, stir and react at room temperature for 3 h, wash, centrifuge and dry the reaction product to obtain an antistatic agent.

[0037] The flame retardant comprises: 7 g of modified aluminum hydroxide, 2 g of phosphaphenanthrene / triazine dibase synergistic flame retardant and 3 g of expanded graphite. The preparation method of the modified aluminum hydroxide comprises: dispersing 10 g of nano aluminum hydroxide into 100 mL of deionized water, and after uniform dispersion, adding 110 g of aluminum triacetylacetonate, reacting at 75° C. for 3 hours. After the reaction is completed, cooling the mixture to room temperature, collecting the solid product by filtration, washing the product with 200 mL of anhydrous ethanol for 3 times, drying the washed product in a vacuum drying oven at 60° C. for 12 hours, grinding the dried product into fine powder, and passing through a 200-mesh sieve to obtain the final modified aluminum hydroxide.

[0038] The preparation method of the antistatic polyethylene composite film is as follows:

[0039] (1) According to the raw material formula of the heat seal layer, the barrier layer and the surface layer, the master batch is respectively batched, mixed and dried for pretreatment; the raw materials of each layer are respectively put into the corresponding twin-screw extruder, and the temperature of the heating zone of the twin-screw extruder is controlled to be 180-200° C., and the melt co-extruded from the die head of the three layers is cooled and solidified on the surface of the casting roller to obtain a cast sheet;

[0040] (2) The cast sheet is longitudinally stretched, the temperature during longitudinal stretching is controlled to be 115°C, the ratio is 3.8:1, and the first heat setting is performed, the temperature of the first heat setting is controlled to be 125°C, and the time is 5s; then the cast sheet is transversely stretched, the temperature during transverse stretching is controlled to be 125°C, the ratio is 3.3:1, and the second heat setting is performed, the temperature of the second heat setting is controlled to be 115°C, and the time is 4s. After the second heat setting, an antistatic polyethylene composite film is obtained.

[0041] Example 2

[0042] This embodiment provides an antistatic polyethylene composite film and a preparation method thereof, which specifically comprises the following steps:

[0043] The antistatic polyethylene composite film includes a heat-sealing layer, a barrier layer and a surface layer, wherein the raw materials of the surface layer and the heat-sealing layer include the following components: 550g of low-density polyethylene, 90g of ultra-high molecular weight polyethylene, 10g of maleic anhydride grafted polyethylene, 60g of antistatic agent and 80g of flame retardant; the barrier layer is ethylene-vinyl alcohol copolymer resin.

[0044] Wherein, the preparation method of the antistatic agent comprises the following steps:

[0045] S1. Prepare graphene oxide by Hummers method. Disperse 9 g of graphene oxide in 90 mL of DMF, add 0.25 L of 2,5(2,6)-di(isocyanate methyl)bicyclo[2.2.1]heptane, and stir the reaction at 60° C. for 4 h under nitrogen protection. After the reaction, wash the reaction product with DMF three times, centrifuge at 6000 rpm for 15 min to collect the product, and vacuum dry the collected product at 50° C. for 12 h to obtain isocyanate-modified graphene.

[0046] S2, dispersing 10g of isocyanate-modified graphene in 100ml of DMF, ultrasonically dispersing for 20min, adding 15g of 5-carboxybenzotriazole and 1g of 1,4-diazabicyclo[2.2.2]octane, stirring the reaction mixture at 70°C for 20h under nitrogen protection, cooling to room temperature after the reaction, washing the reaction product with DMF and ethanol for 3 times respectively, collecting the product by centrifugation at 10000rpm for 30min, and vacuum drying the collected product at 70°C for 48h to obtain benzotriazole-modified graphene;

[0047] S3. Disperse 10 g of benzotriazole-modified graphene in 200 mL of DMF, add 5 g of silver nitrate, stir ultrasonically for 25 min, add 10 g of vitamin C, stir and react at room temperature for 2 h, wash, centrifuge and dry the reaction product to obtain an antistatic agent.

[0048] The flame retardant comprises: 6 g of modified aluminum hydroxide, 1 g of phosphaphenanthrene / triazine dibase synergistic flame retardant and 2 g of expanded graphite. The preparation method of the modified aluminum hydroxide comprises: dispersing 10 g of nano aluminum hydroxide into 100 mL of deionized water, and after uniform dispersion, adding 80 g of aluminum triacetylacetonate, reacting at 70° C. for 4 hours, and after the reaction is completed, cooling the mixture to room temperature, collecting the solid product by filtration, washing the product with 200 mL of anhydrous ethanol for 3 times, drying the washed product in a vacuum drying oven at 60° C. for 12 hours, grinding the dried product into fine powder, and passing through a 200-mesh sieve to obtain the final modified aluminum hydroxide.

[0049] The preparation method of the antistatic polyethylene composite film is as follows:

[0050] (1) According to the raw material formula of the heat seal layer, the barrier layer and the surface layer, the master batch is respectively batched, mixed and dried for pretreatment; the raw materials of each layer are respectively put into the corresponding twin-screw extruder, and the temperature of the heating zone of the twin-screw extruder is controlled to be 180-200° C., and the melt co-extruded from the die head of the three layers is cooled and solidified on the surface of the casting roller to obtain a cast sheet;

[0051] (2) The cast sheet is longitudinally stretched, the temperature during longitudinal stretching is controlled to be 110°C, the ratio is 3.5:1, and the first heat setting is performed, the temperature of the first heat setting is controlled to be 120°C, and the time is 6 seconds; then the cast sheet is transversely stretched, the temperature during transverse stretching is controlled to be 120°C, the ratio is 3:1, and the second heat setting is performed, the temperature of the second heat setting is controlled to be 110°C, and the time is 5 seconds. After the second heat setting, an antistatic polyethylene composite film is obtained.

[0052] Example 3

[0053] This embodiment provides an antistatic polyethylene composite film and a preparation method thereof, which specifically comprises the following steps:

[0054] The antistatic polyethylene composite film includes a heat-sealing layer, a barrier layer and a surface layer, wherein the raw materials of the surface layer and the heat-sealing layer include the following components: 650g of low-density polyethylene, 120g of ultra-high molecular weight polyethylene, 30g of maleic anhydride grafted polyethylene, 100g of antistatic agent and 150g of flame retardant; the barrier layer is ethylene-vinyl alcohol copolymer resin.

[0055] Wherein, the preparation method of the antistatic agent comprises the following steps:

[0056] S1. Prepare graphene oxide by Hummers method. Disperse 11 g of graphene oxide in 110 mL of DMF, add 0.35 L of 2,5(2,6)-di(isocyanate methyl)bicyclo[2.2.1]heptane, and stir the reaction at 100 °C for 1 h under nitrogen protection. After the reaction, wash the reaction product with DMF three times, centrifuge at 6000 rpm for 15 min to collect the product, and dry the collected product in vacuum at 50 °C for 12 h to obtain isocyanate-modified graphene.

[0057] S2, dispersing 10g of isocyanate-modified graphene in 100mL DMF, ultrasonically dispersing for 30min, adding 20g of 5-carboxybenzotriazole and 2g of 1,4-diazabicyclo[2.2.2]octane, stirring the reaction mixture at 85°C for 16h under nitrogen protection, cooling to room temperature after the reaction, washing the reaction product with DMF and ethanol for 3 times respectively, collecting the product by centrifugation at 10000rpm for 30min, and vacuum drying the collected product at 70°C for 48h to obtain benzotriazole-modified graphene;

[0058] S3. Disperse 10 g of benzotriazole-modified graphene in 200 mL of DMF, add 20 g of silver nitrate, stir ultrasonically for 30 min, add 20 g of vitamin C, stir and react at room temperature for 4 h, wash, centrifuge and dry the reaction product to obtain an antistatic agent.

[0059] The flame retardant comprises: 8 g of modified aluminum hydroxide, 3 g of phosphaphenanthrene / triazine dibase synergistic flame retardant and 4 g of expanded graphite. The preparation method of the modified aluminum hydroxide comprises: dispersing 10 g of nano aluminum hydroxide into 100 mL of deionized water, and after uniform dispersion, adding 120 g of aluminum triacetylacetonate, reacting at 80° C. for 2 hours, and after the reaction is completed, cooling the mixture to room temperature, collecting the solid product by filtration, washing the product with 200 mL of anhydrous ethanol for 3 times, drying the washed product in a vacuum drying oven at 60° C. for 12 hours, grinding the dried product into fine powder, and passing through a 200-mesh sieve to obtain the final modified aluminum hydroxide.

[0060] The preparation method of the antistatic polyethylene composite film is as follows:

[0061] (1) According to the raw material formula of the heat seal layer, the barrier layer and the surface layer, the master batch is respectively batched, mixed and dried for pretreatment; the raw materials of each layer are respectively put into the corresponding twin-screw extruder, and the temperature of the heating zone of the twin-screw extruder is controlled to be 180-200° C., and the melt co-extruded from the die head of the three layers is cooled and solidified on the surface of the casting roller to obtain a cast sheet;

[0062] (2) The cast sheet is longitudinally stretched, the temperature during longitudinal stretching is controlled to be 120°C, the ratio is 4:1, and the first heat setting is performed, the temperature of the first heat setting is controlled to be 130°C, and the time is 5s; then the cast sheet is transversely stretched, the temperature during transverse stretching is controlled to be 130°C, the ratio is 3.5:1, and the second heat setting is performed, the temperature of the second heat setting is controlled to be 120°C, and the time is 4s. After the second heat setting, an antistatic polyethylene composite film is obtained.

[0063] Example 4

[0064] This embodiment provides an antistatic polyethylene composite film and a preparation method thereof, which specifically comprises the following steps:

[0065] The antistatic polyethylene composite film includes a heat-sealing layer, a barrier layer and a surface layer, wherein the raw materials of the surface layer and the heat-sealing layer include the following components: 625g of low-density polyethylene, 105g of ultra-high molecular weight polyethylene, 15g of maleic anhydride grafted polyethylene, 90g of antistatic agent and 130g of flame retardant; the barrier layer is ethylene-vinyl alcohol copolymer resin.

[0066] Wherein, the preparation method of the antistatic agent comprises the following steps:

[0067] S1. Prepare graphene oxide by Hummers method. Disperse 10 g of graphene oxide in 100 mL of DMF, add 0.28 L of 2,5(2,6)-di(isocyanate methyl)bicyclo[2.2.1]heptane, and stir the reaction at 70° C. for 2 h under nitrogen protection. After the reaction, wash the reaction product with DMF three times, centrifuge at 6000 rpm for 15 min to collect the product, and dry the collected product in vacuum at 50° C. for 12 h to obtain isocyanate-modified graphene.

[0068] S2, dispersing 10g of isocyanate-modified graphene in 100ml of DMF, ultrasonically dispersing for 30min, adding 16g of 5-carboxybenzotriazole and 1.2g of 1,4-diazabicyclo[2.2.2]octane, stirring the reaction mixture at 75°C for 19h under nitrogen protection, cooling to room temperature after the reaction, washing the reaction product with DMF and ethanol for 3 times respectively, collecting the product by centrifugation at 10000rpm for 30min, and vacuum drying the collected product at 70°C for 48h to obtain benzotriazole-modified graphene;

[0069] S3. Disperse 10 g of benzotriazole-modified graphene in 200 mL of DMF, add 10 g of silver nitrate, stir ultrasonically for 30 min, add 14 g of vitamin C, stir and react at room temperature for 2 h, wash, centrifuge and dry the reaction product to obtain an antistatic agent.

[0070] The flame retardant comprises: 7.5 g of modified aluminum hydroxide, 1.5 g of phosphaphenanthrene / triazine dibase synergistic flame retardant and 2.5 g of expanded graphite. The preparation method of the modified aluminum hydroxide comprises: dispersing 10 g of nano aluminum hydroxide into 100 mL of deionized water, and after uniform dispersion, adding 90 g of aluminum triacetylacetonate, reacting at 78° C. for 2.5 hours, and after the reaction is completed, cooling the mixture to room temperature, collecting the solid product by filtration, washing the product with 200 mL of anhydrous ethanol for 3 times, drying the washed product in a vacuum drying oven at 60° C. for 12 hours, grinding the dried product into fine powder, and passing through a 200-mesh sieve to obtain the final modified aluminum hydroxide.

[0071] The preparation method of the antistatic polyethylene composite film is as follows:

[0072] (1) According to the raw material formula of the heat seal layer, the barrier layer and the surface layer, the master batch is respectively batched, mixed and dried for pretreatment; the raw materials of each layer are respectively put into the corresponding twin-screw extruder, and the temperature of the heating zone of the twin-screw extruder is controlled to be 180-200° C., and the melt co-extruded from the die head of the three layers is cooled and solidified on the surface of the casting roller to obtain a cast sheet;

[0073] (2) The cast sheet is longitudinally stretched, the temperature during longitudinal stretching is controlled to be 115°C, the ratio is 4:1, and the first heat setting is performed, the temperature of the first heat setting is controlled to be 125°C, and the time is 5s; then the cast sheet is transversely stretched, the temperature during transverse stretching is controlled to be 125°C, the ratio is 3:1, and the second heat setting is performed, the temperature of the second heat setting is controlled to be 115°C, and the time is 5s. After the second heat setting is completed, an antistatic polyethylene composite film is obtained.

[0074] Comparative Example 1

[0075] This comparative example provides an antistatic polyethylene composite film and a preparation method thereof, which specifically comprises the following steps:

[0076] The antistatic polyethylene composite film includes a heat-sealing layer, a barrier layer and a surface layer, wherein the raw materials of the surface layer and the heat-sealing layer include the following components: 600g of low-density polyethylene, 110g of ultra-high molecular weight polyethylene, 20g of maleic anhydride grafted polyethylene, 80g of antistatic agent and 110g of flame retardant; the barrier layer is ethylene-vinyl alcohol copolymer resin.

[0077] Wherein, the preparation method of the antistatic agent comprises the following steps:

[0078] S1. Prepare graphene oxide by Hummers method. Disperse 10 g of graphene oxide in 100 mL of DMF, add 0.3 L of 2,5(2,6)-di(isocyanate methyl)bicyclo[2.2.1]heptane, and stir the reaction at 80° C. for 2.5 h under nitrogen protection. After the reaction, wash the reaction product with DMF three times, centrifuge at 6000 rpm for 15 min to collect the product, and dry the collected product in vacuum at 50° C. for 12 h to obtain isocyanate-modified graphene.

[0079] S2. Disperse 10 g of isocyanate-modified graphene in 200 mL of DMF, add 15 g of silver nitrate, stir ultrasonically for 25 min, add 15 g of vitamin C, stir and react at room temperature for 3 h, wash, centrifuge and dry the reaction product to obtain silver-loaded isocyanate-modified graphene, which is an antistatic agent.

[0080] The flame retardant comprises: 7 g of modified aluminum hydroxide, 2 g of phosphaphenanthrene / triazine dibase synergistic flame retardant and 3 g of expanded graphite. The preparation method of the modified aluminum hydroxide comprises: dispersing 10 g of nano aluminum hydroxide into 100 mL of deionized water, and after uniform dispersion, adding 110 g of aluminum triacetylacetonate, reacting at 75° C. for 3 hours. After the reaction is completed, cooling the mixture to room temperature, collecting the solid product by filtration, washing the product with 200 mL of anhydrous ethanol for 3 times, drying the washed product in a vacuum drying oven at 60° C. for 12 hours, grinding the dried product into fine powder, and passing through a 200-mesh sieve to obtain the final modified aluminum hydroxide.

[0081] The preparation method of the antistatic polyethylene composite film is as follows:

[0082] (1) According to the raw material formula of the heat seal layer, the barrier layer and the surface layer, the master batch is respectively batched, mixed and dried for pretreatment; the raw materials of each layer are respectively put into the corresponding twin-screw extruder, and the temperature of the heating zone of the twin-screw extruder is controlled to be 180-200° C., and the melt co-extruded from the die head of the three layers is cooled and solidified on the surface of the casting roller to obtain a cast sheet;

[0083] (2) The cast sheet is longitudinally stretched, the temperature during longitudinal stretching is controlled to be 115°C, the ratio is 3.8:1, and the first heat setting is performed, the temperature of the first heat setting is controlled to be 125°C, and the time is 5s; then the cast sheet is transversely stretched, the temperature during transverse stretching is controlled to be 125°C, the ratio is 3.3:1, and the second heat setting is performed, the temperature of the second heat setting is controlled to be 115°C, and the time is 4s. After the second heat setting, an antistatic polyethylene composite film is obtained.

[0084] Comparative Example 2

[0085] This embodiment provides an antistatic polyethylene composite film and a preparation method thereof, which specifically comprises the following steps:

[0086] The antistatic polyethylene composite film includes a heat-sealing layer, a barrier layer and a surface layer, wherein the raw materials of the surface layer and the heat-sealing layer include the following components: 600g of low-density polyethylene, 110g of ultra-high molecular weight polyethylene, 20g of maleic anhydride grafted polyethylene, 80g of antistatic agent and 110g of flame retardant; the barrier layer is ethylene-vinyl alcohol copolymer resin.

[0087] Wherein, the preparation method of the antistatic agent comprises the following steps:

[0088] S1. Prepare graphene oxide by Hummers method. Disperse 10 g of graphene oxide in 100 mL of DMF, add 0.3 L of 2,5(2,6)-di(isocyanate methyl)bicyclo[2.2.1]heptane, and stir the reaction at 80° C. for 2.5 h under nitrogen protection. After the reaction, wash the reaction product with DMF three times, centrifuge at 6000 rpm for 15 min to collect the product, and dry the collected product in vacuum at 50° C. for 12 h to obtain isocyanate-modified graphene.

[0089] S2, dispersing 10g of isocyanate-modified graphene in 200mL of DMF, adding 15g of silver nitrate, stirring ultrasonically for 25min, adding 15g of vitamin C, stirring and reacting at room temperature for 3h, washing, centrifuging and drying the reaction product to obtain silver-loaded isocyanate-modified graphene;

[0090] S3. Disperse 10 g of silver-loaded isocyanate-modified graphene in 100 mL of DMF, perform ultrasonic dispersion for 25 min, add 18 g of 5-carboxybenzotriazole and 1.5 g of 1,4-diazabicyclo[2.2.2]octane, and stir the reaction mixture at 80 °C for 18 h under nitrogen protection. After the reaction is completed, cool to room temperature, wash the reaction product with DMF and ethanol for 3 times respectively, collect the product by centrifugation at 10,000 rpm for 30 min, and dry the collected product in vacuum at 70 °C for 48 h to obtain the antistatic agent.

[0091] The flame retardant comprises: 7 g of modified aluminum hydroxide, 2 g of phosphaphenanthrene / triazine dibase synergistic flame retardant and 3 g of expanded graphite. The preparation method of the modified aluminum hydroxide comprises: dispersing 10 g of nano aluminum hydroxide into 100 mL of deionized water, and after uniform dispersion, adding 110 g of aluminum triacetylacetonate, reacting at 75° C. for 3 hours. After the reaction is completed, cooling the mixture to room temperature, collecting the solid product by filtration, washing the product with 200 mL of anhydrous ethanol for 3 times, drying the washed product in a vacuum drying oven at 60° C. for 12 hours, grinding the dried product into fine powder, and passing through a 200-mesh sieve to obtain the final modified aluminum hydroxide.

[0092] The preparation method of the antistatic polyethylene composite film is as follows:

[0093] (1) According to the raw material formula of the heat seal layer, the barrier layer and the surface layer, the master batch is respectively batched, mixed and dried for pretreatment; the raw materials of each layer are respectively put into the corresponding twin-screw extruder, and the temperature of the heating zone of the twin-screw extruder is controlled to be 180-200° C., and the melt co-extruded from the die head of the three layers is cooled and solidified on the surface of the casting roller to obtain a cast sheet;

[0094] (2) The cast sheet is longitudinally stretched, the temperature during longitudinal stretching is controlled to be 115°C, the ratio is 3.8:1, and the first heat setting is performed, the temperature of the first heat setting is controlled to be 125°C, and the time is 5s; then the cast sheet is transversely stretched, the temperature during transverse stretching is controlled to be 125°C, the ratio is 3.3:1, and the second heat setting is performed, the temperature of the second heat setting is controlled to be 115°C, and the time is 4s. After the second heat setting, an antistatic polyethylene composite film is obtained.

[0095] Comparative Example 3

[0096] This comparative example provides an antistatic polyethylene composite film and a preparation method thereof, which specifically comprises the following steps:

[0097] The antistatic polyethylene composite film includes a heat-sealing layer, a barrier layer and a surface layer, wherein the raw materials of the surface layer and the heat-sealing layer include the following components: 600g of low-density polyethylene, 110g of ultra-high molecular weight polyethylene, 20g of maleic anhydride grafted polyethylene, 80g of antistatic agent and 110g of flame retardant; the barrier layer is ethylene-vinyl alcohol copolymer resin.

[0098] Wherein, the preparation method of the antistatic agent comprises the following steps:

[0099] S1. Prepare graphene oxide by Hummers method. Disperse 10 g of graphene oxide in 100 mL of DMF, add 0.3 L of 2,5(2,6)-di(isocyanate methyl)bicyclo[2.2.1]heptane, and stir the reaction at 80° C. for 2.5 h under nitrogen protection. After the reaction, wash the reaction product with DMF three times, centrifuge at 6000 rpm for 15 min to collect the product, and dry the collected product in vacuum at 50° C. for 12 h to obtain isocyanate-modified graphene.

[0100] S2, dispersing 10g of isocyanate-modified graphene in 100mL DMF, ultrasonically dispersing for 25min, adding 18g of 5-carboxybenzotriazole and 1.5g of 1,4-diazabicyclo[2.2.2]octane, stirring the reaction mixture at 80°C for 18h under nitrogen protection, cooling to room temperature after the reaction, washing the reaction product with DMF and ethanol for 3 times respectively, collecting the product by centrifugation at 10000rpm for 30min, and vacuum drying the collected product at 70°C for 48h to obtain benzotriazole-modified graphene;

[0101] S3. Disperse 10 g of benzotriazole-modified graphene in 200 mL of DMF, add 15 g of silver nitrate, stir ultrasonically for 25 min, add 15 g of vitamin C, stir and react at room temperature for 3 h, wash, centrifuge and dry the reaction product to obtain an antistatic agent.

[0102] The flame retardant comprises: 7g of aluminum hydroxide and 2g of phosphaphenanthrene / triazine dibase synergistic flame retardant.

[0103] The preparation method of the antistatic polyethylene composite film is as follows:

[0104] (1) According to the raw material formula of the heat seal layer, the barrier layer and the surface layer, the master batch is respectively batched, mixed and dried for pretreatment; the raw materials of each layer are respectively put into the corresponding twin-screw extruder, and the temperature of the heating zone of the twin-screw extruder is controlled to be 180-200° C., and the melt co-extruded from the die head of the three layers is cooled and solidified on the surface of the casting roller to obtain a cast sheet;

[0105] (2) The cast sheet is longitudinally stretched, the temperature during longitudinal stretching is controlled to be 115°C, the ratio is 3.8:1, and the first heat setting is performed, the temperature of the first heat setting is controlled to be 125°C, and the time is 5s; then the cast sheet is transversely stretched, the temperature during transverse stretching is controlled to be 125°C, the ratio is 3.3:1, and the second heat setting is performed, the temperature of the second heat setting is controlled to be 115°C, and the time is 4s. After the second heat setting, an antistatic polyethylene composite film is obtained.

[0106] Performance Testing

[0107] The properties of the polyethylene films prepared in the comparative examples and the examples were tested. The surface resistivity and volume resistivity of the composite films were tested according to GB / T1410-2006. The flame retardancy of the composite films was tested according to UL 94 standard. The test results are shown in Table 1.

[0108] Table 1 Performance test

[0109] Flame retardant grade UL94 Surface resistivity / Ω·m Volume resistivity / Ω·m Example 1 V-0 <![CDATA[2.7×10 9 ]]> <![CDATA[3.0×10 10 ]]> Example 2 V-1 <![CDATA[4.8×10 9 ]]> <![CDATA[5.1×10 10 ]]> Example 3 V-0 <![CDATA[1.6×10 9 ]]> <![CDATA[2.2×10 10 ]]> Example 4 V-0 <![CDATA[2.1×10 9 ]]> <![CDATA[2.4×10 10 ]]> Comparative Example 1 V-1 <![CDATA[3.4×10 10 ]]> <![CDATA[5.0×10 11 ]]> Comparative Example 2 V-1 <![CDATA[2.9×10 10 ]]> <![CDATA[3.4×10 11 ]]> Comparative Example 3 V-2 <![CDATA[7.5×10 9 ]]> <![CDATA[9.1×10 10 ]]>

[0110] It can be seen from Table 1 that the composite film prepared by the present invention has good antistatic and flame retardant properties. Compared with Comparative Examples 1-3, the addition of antistatic agent, modified aluminum hydroxide, phosphaphenanthrene / triazine dibase synergistic flame retardant and expanded graphite can significantly improve the antistatic and flame retardant properties of the polyethylene composite film.

[0111] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An antistatic polyethylene composite film, which is provided with a heat sealing layer, a barrier layer and a surface layer in sequence from the inside to the outside, characterized in that: The raw materials of the surface layer and the heat-sealing layer include the following components by weight: 55-65 parts of low-density polyethylene, 9-12 parts of ultra-high molecular weight polyethylene, 1-3 parts of compatibilizer, 6-10 parts of antistatic agent and 8-15 parts of flame retardant; the barrier layer is ethylene-vinyl alcohol copolymer resin.

2. The antistatic polyethylene composite film according to claim 1, characterized in that: The preparation method of the antistatic agent comprises the following steps: S1. Graphene oxide is prepared by Hummers method. Graphene oxide is dispersed in DMF, 2,5(2,6)-bis(isocyanate methyl)bicyclo[2.2.1]heptane is added, and the mixture is stirred at 60-100° C. for 1-4 h. The reaction product is washed, centrifuged and dried to obtain isocyanate-modified graphene. S2, dispersing the isocyanate-modified graphene in DMF, ultrasonically dispersing for 20-30 minutes, adding 5-carboxybenzotriazole and a catalyst, stirring the reaction mixture at 70-85° C. for 16-20 hours under nitrogen protection, cooling to room temperature after the reaction is completed, washing, centrifuging and drying the reaction product to obtain benzotriazole-modified graphene; S3, dispersing the benzotriazole-modified graphene in DMF, adding silver nitrate, ultrasonically stirring, adding a reducing agent, stirring for reaction, washing, centrifuging and drying the reaction product, and obtaining the antistatic agent.

3. The antistatic polyethylene composite film according to claim 2, characterized in that: In step S1, graphene oxide and 2,5(2,6)-bis(isocyanatomethyl)bicyclo[ 2.2.1] The mass volume ratio of heptane is 90-110 mg:2.5-3.5 mL.

4. The antistatic polyethylene composite film according to claim 2, characterized in that: In step S2, the mass ratio of isocyanate-modified graphene, 5-carboxybenzotriazole and catalyst is 1:1.5-2:0.1-0.2, and the catalyst is 1,4-diazabicyclo[2.2.2]octane.

5. The antistatic polyethylene composite film according to claim 2, characterized in that: In step S3, the mass ratio of benzotriazole-modified graphene, silver nitrate and reducing agent is 1:0.5-2:1-2, and the reducing agent is vitamin C or sodium borohydride.

6. The antistatic polyethylene composite film according to claim 1, characterized in that: The flame retardant comprises, by weight, 6-8 parts of modified aluminum hydroxide, 1-3 parts of phosphaphenanthrene / triazine dibase synergistic flame retardant and 2-4 parts of expanded graphite.

7. The antistatic polyethylene composite film according to claim 6, characterized in that: The preparation method of the modified aluminum hydroxide comprises the following steps: dispersing nano aluminum hydroxide into deionized water, adding aluminum triacetylacetonate after the dispersion is uniform, reacting at 70-80° C. for 2-4 hours, filtering, washing and drying the reaction product to obtain the modified aluminum hydroxide.

8. The antistatic polyethylene composite film according to claim 7, characterized in that: The mass ratio of the nano aluminum hydroxide to aluminum triacetylacetonate is 1:8-12.

9. The antistatic polyethylene composite film according to claim 1, characterized in that: The compatibilizer is any one of maleic anhydride grafted polyethylene and ethylene-acrylic acid copolymer.

10. The method for preparing an antistatic polyethylene composite film according to any one of claims 1 to 9, characterized in that: The steps include: (1) According to the raw material formula of the heat seal layer, the barrier layer and the surface layer, the master batch is respectively batched, mixed and dried for pretreatment; the raw materials of each layer are respectively put into the corresponding twin-screw extruder, and the temperature of the heating zone of the twin-screw extruder is controlled to be 180-200° C., and the melt co-extruded from the die head of the three layers is cooled and solidified on the surface of the casting roller to obtain a cast sheet; (2) The cast sheet is longitudinally stretched, the temperature during longitudinal stretching is controlled to be 110-120°C, the ratio is 3.5-4:1, and the first heat setting is performed, the temperature of the first heat setting is controlled to be 120-130°C, and the time is 5-6s; then the cast sheet is transversely stretched, the temperature during transverse stretching is controlled to be 120-130°C, the ratio is 3-3.5:1, and the second heat setting is performed, the temperature of the second heat setting is controlled to be 110-120°C, and the time is 4-5s. After the second heat setting is completed, an antistatic polyethylene composite film is obtained.

Citation Information

Patent Citations

  • Three-layer co-extruded rapid bidirectionally stretched wide polyethylene composite film and preparation method thereof

    CN106183292A

  • Antibacterial medical glove and preparation method thereof

    CN107298826A

  • Fatigue-resistant flame-retardant PVC (polyvinyl chloride) plastic boot

    CN115011046A

  • PE multilayer barrier composite film and preparation method thereof

    CN115625956A

  • Antistatic polyethylene composite material as well as preparation method and application thereof

    CN115710394A

Cited By

  • Antistatic polyester composite current collector film and preparation method thereof

    CN122465324A